2019
DOI: 10.1021/acs.jmedchem.9b00318
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Lead-Optimization of 4,5-Dihydropyrazoles as Mono-Kinase Selective, Orally Bioavailable and Efficacious Inhibitors of Receptor Interacting Protein 1 (RIP1) Kinase

Abstract: RIP1 kinase regulates necroptosis and inflammation and may play an important role in contributing to a variety of human pathologies, including inflammatory and neurological diseases. Currently, RIP1 kinase inhibitors have advanced into early clinical trials for evaluation in inflammatory diseases such as psoriasis, rheumatoid arthritis, and ulcerative colitis and neurological diseases such as amyotrophic lateral sclerosis and Alzheimer's disease. In this paper, we report on the design of potent and highly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…To date, GSK2982772 has not shown significant therapeutic benefit in psoriasis or rheumatoid arthritis, while the data from the ulcerative colitis trial are not yet available (ClinicaTrials.gov). In addition to inflammatory diseases, GSK tested RIP1 inhibitor, GSK3145095, in clinical trial intended to test RIP1 inhibition in pancreatic and other solid tumors (Harris et al , 2019), but was terminated during patient recruitment. DNL104, Denali’s brain‐penetrant RIP1 inhibitor, did not trigger any adverse effects in central nervous system, although they observed abnormal liver function in some healthy subjects (Grievink et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, GSK2982772 has not shown significant therapeutic benefit in psoriasis or rheumatoid arthritis, while the data from the ulcerative colitis trial are not yet available (ClinicaTrials.gov). In addition to inflammatory diseases, GSK tested RIP1 inhibitor, GSK3145095, in clinical trial intended to test RIP1 inhibition in pancreatic and other solid tumors (Harris et al , 2019), but was terminated during patient recruitment. DNL104, Denali’s brain‐penetrant RIP1 inhibitor, did not trigger any adverse effects in central nervous system, although they observed abnormal liver function in some healthy subjects (Grievink et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, RIPK1 is expressed in all major cell types (Ofengeim et al, 2015;Zhang et al, 2014). RIPK1 kinase activity has been implicated in the pathology associated with CNS diseases, including Alzheimer's disease (Ofengeim et al, 2017), amyotrophic lateral sclerosis (ALS) (Ito et al, 2016;Xu et al, 2018), Niemann-Pick disease type C (Cougnoux et al, 2018), and MS (Harris et al, 2019;Ofengeim et al, 2015;Yoshikawa et al, 2018;Zhang et al, 2019). The kinase activity of RIPK1 regulates both caspase-independent necroptotic death via RIPK3 and mixed lineage kinase domain-like (MLKL) and RIPK1-kinase-dependent apoptosis (RDA) via caspase-8, and emerging evidence suggests RIPK1 can also regulate proinflammatory cytokine and chemokine production (Najjar et al, 2016;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RIPK1 kinase activity emerged as driver of ischemic injury [18][19][20] as well as neurodegenerative diseases such as multiple sclerosis (MS) 21 , ALS (amyotrophic lateral sclerosis) 22 and Alzheimer's disease 23 . These studies identified RIPK1 kinase activity as a key factor contributing to the pathogenesis of inflammatory diseases, prompting the development of RIPK1 kinase inhibitors [24][25][26][27][28] that reached clinical trials for the treatment of inflammatory and neurodegenerative diseases as well as pancreatic cancer 24,25 .…”
mentioning
confidence: 99%